New species and new records of Terebellidae (Annelida: Terebelliformia) from off the Brazilian coast - Carrerette, Orlemir; Nogueira, João Miguel De Matos (Zootaxa, 2015)
Three new species of Terebellidae Grube, 1850 were identified among material collected on hard substrates off the states of Paraíba and Pernambuco, northeastern Brazil. These species are Lanicola hutchingsae sp. nov., Eupolymnia corae sp. nov., and Neoleprea potiguara sp. nov., all herein described and compared with the morphologically most similar congeners. Lanicola hutchingsae sp. nov., is characterized by having lobes of segment 2–3 reaching beyond segment 1, with dorsal margin extending dorsally, covering bases of branchiae, and uncini with 3 rows of secondary teeth above main fang. Eupolymnia corae sp. nov., has lobes of segment 2 laterally higher, with dorsal margins rounded, and lobes of segments 3 and 4 progressively shorter, roughly triangular, with pointed tips, pairs of branchiae progressively shorter, all longitudinally aligned, and uncini throughout with 3 rows of secondary teeth above main fang. Neoleprea potiguara sp. nov., is characterized by having notopodia up to the segment 23, with nephridial papillae on segment 3 and genital papillae on segments 6–19. These are the first records for the genera Lanicola Hartmann-Schröder, 1986 and Neoleprea Hessle, 1917 in Brazilian waters.